E-victimization and e-predation theory as the dominant aggressive communication: the case of cyber bullying. Issue 3 (27th May 2019) - Wagner, Anne
ABSTRACT: The paper will focus on the identification of several key criteria in e-discourses via the constitution of e-images of the Anonymous arising from e-medias (Facebook, twitter, Snapchat, WeChat, etc.) with a specific focus on youngsters and their (ab)uses of these communication channels to facilitate digital predation, and so to lead to e-victimization. I will explain the specifics of e-victimization discourse taking into consideration its triadic dimension. I will then be able to conceptualize a dominant e-communication and the e-victimization theory around central ideas of dynamics of violence, gender discrimination and power abuse leading to a semio-sphere with a deep focus on anonymity, exposure, frequency, and insecurity as indicators of collective e-delinquency and proneness to e-victimization.